The relationship of task self-efficacy and role efficacy beliefs to role performance in Spanish youth soccer - Bray, S. R.; Balaguer, I.; Duda, J. L. (Journal of Sports Sciences, 2004)
The aim of this study was to examine the relationship between role efficacy and role performance after controlling for the effects of task self-efficacy. Two hundred and ninety-five Spanish youth soccer players from 20 teams completed self-report measures of task self-efficacy, role efficacy and role performance at the mid-point of a competitive season. The 20 team coaches also provided ratings of each of their players' role performances at mid-season. Consistent with hypotheses, bivariate correlations showed task self-efficacy and role efficacy were positively related to role performance ratings. Hierarchical regression analyses revealed that role efficacy contributed significantly to the prediction of athletes' ratings of role performance after controlling for task self-efficacy. Role efficacy also explained significant variation in the prediction of coach ratings; however, the effects were less dramatic and inconsistent. Our results support self-efficacy theory and reinforce the value of assessing efficacy beliefs representing behaviours carried out both independently and interdependently for the prediction of role performance within team environments. Future research directions are proposed.